Dorosły z niepełnosprawnością intelektualną w sieci systemu instytucjonalnego: analiza wybranych problemów - Fetzki, Tomasz; Fetzka, Agnieszka (Adult Education Discourses, 2020)
This article is a voice in the discussion on irregularities in the operation of the institutional support system for adults with intellectual disabilities, who, due to the specificity of their dysfunction, face fundamental problems in the process of obtaining social autonomy. Often the institutions established to support this process, due to shortcomings of properly educated staff, are not able to perform their tasks properly. The text, in the form of a case study presentation, analyses these phenomena and attempts to indicate the sources of evil inherent in the system.